Dakwahtainment's Impact on Establishing Religious Harmony - Yulya Cahyany Pranata; Andini Nur Bahri (Reslaj : Religion Education Social Laa Roiba Journal, 2023)
Since modern da'wah was implemented in new media, da'wahtainment designs have long existed in people's lives, and various responses have emerged. This dakwahtainment affects religious harmony in addition to Muslims. However, the practice of preaching in new media in an effort to achieve religious harmony has received very little research attention. The purpose of this study is to provide an overview of the extent to which propaganda can serve as a substitute for fostering tolerance and reducing conflicts between religions. This study employs a quantitative approach by distributing a questionnaire to 272 religiously diverse respondents from various Indonesian cities participating in the study. The data demonstrate that Dakwahtainment significantly improves the Religious Harmony variable. The fact that the Dakwahtainment variable has a positive coefficient of 0.382 indicates that it influences the Religious Harmony variable positively. Keyword: Tolerance, religious harmony, and dakwahtainment